Antioxidant phenolic compounds recovery from Mangifera indica L. by-products by supercritical antisolvent extraction. (October 2015) - Meneses, Miguel A.; Caputo, Giuseppe; Scognamiglio, Mariarosa; Reverchon, Ernesto; Adami, Renata
Highlights: Use of mango by-products as source of antioxidant compounds. SAE is effective for recovering of antioxidants from ethanolic extract. Nanoparticles of antioxidants increases the dissolution rate of polyphenols. The antioxidant activity was maintained after processing at supercritical conditions. Abstract: Supercritical Antisolvent Extraction (SAE) was used in the recovery of antioxidant compounds from mango by-products. The antioxidant extract was obtained by solid–liquid extraction using aqueous acetone (80% v/v) and subsequent adsorption/desorption in C18 cartridge. Recovery of antioxidants was performed by SAE using SC-CO2 as antisolvent. The temperature and pressure parameters were varied in the range 35–45 °C and 8–15 MPa. The SAE process allowed the recovery of about 90% of the initial phenolic compounds, the best recovery was obtained at 40 °C and 10 MPa and the main compounds were mangiferin, isomangiferin, quercetin 3-O-galactoside, quercetin 3-O-glucoside, quercetin 3-O-xyloside, quercetin 3-O-arabinoside, quercetin and kaempferol. The product obtained was a dry powder, spherical nanoparticles with a particle diameter of 143 ± 40 nm with an antioxidant activity of 851.9 μMol TE/g and a half inhibition concentration of DPPH radical of 90 μg/mL. The analyses performed indicated that SAE processing of natural extracts is effective for improving the activity of natural antioxidant compounds by producing nanoparticles.